2003
DOI: 10.4049/jimmunol.171.8.4294
|View full text |Cite
|
Sign up to set email alerts
|

A Dominant Role of Toll-Like Receptor 4 in the Signaling of Apoptosis in Bacteria-Faced Macrophages

Abstract: Conserved bacterial components potently activate host immune cells through transmembrane Toll-like receptors (TLRs), which trigger a protective immune response but also may signal apoptosis. In this study, we investigated the roles of TLR2 and TLR4 as inducers of apoptosis in Yersinia enterocolitica-infected macrophages. Yersiniae suppress activation of the antiapoptotic NF-κB signaling pathway in host cells by inhibiting inhibitory κB kinase-β. This leads to macrophage apoptosis under infection conditions. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
129
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(140 citation statements)
references
References 81 publications
8
129
2
Order By: Relevance
“…The slight reduction in IFN-␤ mRNA expression observed in TRIF-deficient cells is in sharp contrast to the complete lack of IFN-␤ synthesis and Stat1 tyrosine phosphorylation caused by TRIF deficiency after TLR3 stimulation and by TRIF or TRAM deficiency after TLR4 stimulation (35,36). Besides supporting the notion that IFN-␤ production and IFN-␤-mediated death sensitization are TLR-independent events, our analyses of infected macrophages show that the mechanism of death induction by L. monocytogenes differs from that used by Yersinia enterolytica, Bacillus anthracis, or the sipB mutant of Salmonella typhimurium, which in all cases requires signaling through TLR4 (69,70).…”
Section: Figurementioning
confidence: 64%
“…The slight reduction in IFN-␤ mRNA expression observed in TRIF-deficient cells is in sharp contrast to the complete lack of IFN-␤ synthesis and Stat1 tyrosine phosphorylation caused by TRIF deficiency after TLR3 stimulation and by TRIF or TRAM deficiency after TLR4 stimulation (35,36). Besides supporting the notion that IFN-␤ production and IFN-␤-mediated death sensitization are TLR-independent events, our analyses of infected macrophages show that the mechanism of death induction by L. monocytogenes differs from that used by Yersinia enterolytica, Bacillus anthracis, or the sipB mutant of Salmonella typhimurium, which in all cases requires signaling through TLR4 (69,70).…”
Section: Figurementioning
confidence: 64%
“…A few samples of primary blast lines obtained from patients with AML also responded to the additive effects of LPS and IFN-α, indicating that sensitivity to TLR4-mediated inducible apoptosis is found in a fraction of AML samples with no correlation with FAB phenotypes [74]. It has been observed that cells stimulated with TLR ligands udergo programmed cell death after NF-κB activation by Fas-associated death domain protein (FADD) and subsequent caspase recruitment [75][76][77][78]. This phenomenon reflects the regulatory capacity of TLR signaling protecting the host from excessive proliferation of immunecompetent cells being activated during inflammatory reactions, and may be implicated in an anti-tumor response enhanced with TLR stimulation.…”
Section: The Results Of Tlr Activation -Tlrs In Carcinogenesismentioning
confidence: 99%
“…To overexpress ubiquitin for the YopE and ubiquitin IP experiments, HEK293 cells were seeded in six-well cell culture plates and transfected with a human cDNA construct encoding an octameric tandem fusion of hemagglutinin-ubiquitin (35) or empty control vector. Transfections were conducted by the calcium-phosphate transfection method, as described (36). The ubiquitin expression vector was provided by M. Treier (European Molecular Biology Laboratory, Heidelberg, Germany).…”
Section: Western Blot (Wb) Immunoprecipitation (Ip) and Cell Transfmentioning
confidence: 99%